2014
DOI: 10.1007/s11481-013-9520-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neurotrophic Factor Alterations in the Neurodegenerative Process in HIV Associated Neurocognitive Disorders

Abstract: Migration of HIV infected cells into the CNS is associated with a spectrum of neurological disorders, ranging from milder forms of HIV-associated neurocognitive disorders (HAND) to HIV-associated dementia (HAD). These neuro-psychiatric syndromes are related to the neurodegenerative pathology triggered by the release of HIV proteins and cytokine/chemokines from monocytes/macrophages into the CNS –a condition known as HIV encephalitis (HIVE). As a result of more effective combined anti-retroviral therapy (cART) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 187 publications
(233 reference statements)
2
42
0
Order By: Relevance
“…This review highlights the key role of targeting FGF2/FGFR1 axis as a therapeutic intervention for CNS diseases (aging and HAND), with the goal of promoting neurogenesis, restoring synaptic plasticity and modulating neuron-glial interactions and inflammation. A comprehensive review by Fields et.al further corroborates the role of FGF1 and FGF2 in neuroprotection against toxicity mediated by HIV proteins in both cell culture and rodent models (Fields et al, 2014). These authors have elegantly discussed how aging and HIV interact to affect various neurotrophins via different mechanisms.…”
Section: Growth Factor Mimetics and Antagonists As Therapeuticsmentioning
confidence: 85%
“…This review highlights the key role of targeting FGF2/FGFR1 axis as a therapeutic intervention for CNS diseases (aging and HAND), with the goal of promoting neurogenesis, restoring synaptic plasticity and modulating neuron-glial interactions and inflammation. A comprehensive review by Fields et.al further corroborates the role of FGF1 and FGF2 in neuroprotection against toxicity mediated by HIV proteins in both cell culture and rodent models (Fields et al, 2014). These authors have elegantly discussed how aging and HIV interact to affect various neurotrophins via different mechanisms.…”
Section: Growth Factor Mimetics and Antagonists As Therapeuticsmentioning
confidence: 85%
“…T helper cells (Th1 and Th2) secrete MMP9 [45], which plays a critical role in the migration of T cells from the blood stream to the brain and other tissues [46, 47]. Additionally, recent advances in neuro-inflammation implicate abnormal neurotrophic factor signaling, including fibroblast growth factors (FGFs) in HIV-associated neurocognitive decline (HAND) [48] and stroke [49]. The increase in CNS FGF levels after resveratrol treatment suggests an effect on growth factors, which may play a role in neuro-resilience in aging and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated impaired processing and transport of neurotrophic factors in HIV-1 neuropathogenesis [81-83]. The PI3K-mTOR signaling pathway is involved in synaptic plasticity [84-86] and was shown to be dysregulated in the frontal cortex of patients with neuroAIDS [43].…”
Section: Discussionmentioning
confidence: 99%